Proliferative Diabetic Retinopathy - Syarifah Rohaya; Fikri Haikal (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Diabetic retinopathy is the most common cause of blindness found in adults between 20 and 74 years of age, where diabetic patients have a risk of being 25 times more likely to develop complications than nondiabetics. Diabetes mellitus (DM) is a group of metabolic diseases with characteristic hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action or both. Chronic hyperglycemia in diabetes is associated with long-term damage, dysfunction or failure of several organs, especially the eyes, kidneys, nerves, heart, and blood vessels. Treatment for diabetic retinopathy relies almost exclusively on the management of metabolic dysregulation of diabetes mellitus until the severity of vascular lesions required laser surgery